2018
DOI: 10.3389/fvets.2018.00311
|View full text |Cite
|
Sign up to set email alerts
|

Agmatine for Pain Management in Dogs With Coxofemoral Joint Osteoarthritis: A Pilot Study

Abstract: Background: Pain from coxofemoral joint (CFJ) osteoarthritis (OA) characteristic of canine hip dysplasia (CHD) afflicts many dogs. Intervertebral disc (IVD) degeneration is a common CFJ OA comorbidity. Non-steroidal anti-inflammatory drug (NSAID) administration is standard for treatment of pain from degenerative joint disease. Potential side effects and tolerance from prolonged administration drive efforts to identify compounds that may be alternatives to or combined with NSAIDs. Agmatine, decarboxylated argin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…In veterinary medicine, a wide range of applications for the evaluation of ground reaction forces can be found. In addition to research on the physiological movement patterns of various species [1,2], such evaluations serve as a valuable tool in the investigation of orthopedic and neurologic diseases of dogs [3,4] and enable new findings in therapy [5]. In human medicine, the measurement of the center of pressure (COP) is also frequently used to examine patients with orthopedic or neurological diseases [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary medicine, a wide range of applications for the evaluation of ground reaction forces can be found. In addition to research on the physiological movement patterns of various species [1,2], such evaluations serve as a valuable tool in the investigation of orthopedic and neurologic diseases of dogs [3,4] and enable new findings in therapy [5]. In human medicine, the measurement of the center of pressure (COP) is also frequently used to examine patients with orthopedic or neurological diseases [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The median arthrosis score in our study was 2 with a range from 1 to 3 for the TG and PG. Taguchi et al (34) found nutraceutical treatment efficacy on coxofemoral joint OA among low-grades but not high-grades. Farrell et al (35) demonstrated that dogs with a higher grade of radiographic arthrosis had a significantly higher score of cartilage pathology compared to dogs with a low grade of radiographic arthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Taguchi et al (2018), a displasia de quadril está entre as condições ortopédicas degenerativas mais comuns em animais de companhia, iniciando, em geral, por alterações na cápsula da articulação coxofemoral com progressão para degeneração articular. É caracterizada pela incongruência e instabilidade das articulações (NUNEZ et al, 2020) e, esta anormalidade do desenvolvimento das articulações, tem como principal achado a osteoartrite em cães idosos que é acompanhada pelos estímulos nociceptivos da dor (MATSUBARA et al, 2019).…”
Section: Displasia De Quadrilunclassified